Tettegouche State Park Summer Visitors’ Perceptions on Ecosystem Services of the Park and Management Practices They Support - Varnaci Uzun, Funda; Gilbertson, Kenneth L. (European Journal of Sustainable Development, 2017)
It has been said that youth and their parents are losing their connection to nature as evidenced by attendance in protected nature areas (PNA’s) such as state and national parks (Outdoor Foundation, 2010, 2014; Monz, Cole, Leung & Marion, 2010). Managers have increased their efforts to encourage greater attendance through advertisements and specialized programs. A challenge to park managers is to manage the park in a manner that protects the natural resource while also managing the visitor experience (Francis, 2016; Lofthouse & Simmons, 2016). A primary benefit of a PNA to a visitor exists through Ecosystem Services, which is an outcome of the quality of the park experience (MEA, 2005). The quality of the visitor experience is determined to be beneficial to ones quality of life or sense of well-being (Diversitas, 2016). Using a survey design, we queired park visitors at one of the most popular state parks in the state of Minnesota called Tettegouche State Park. Visitors (n=222) were administered a questionnaire during two weeks in August, 2013, which is peak season. We asked respondents about the purpose and quality of their visit. Additionally, visitors’ perceptions of ecosystem services related to the park were asked (e.g. “I believe that Tettegouche State Park is particularly important because it is a place of scenic beauty”). The ecosystem services items were based on the Common International Classification of Ecosystem Services (CICES, 2013, 2016). Analysis used descriptive statistics and a factor analysis to determine groupings of perceived ecosystem services and management actions. Results indicated a positive park experience with respondents indicating that they intended to revisit the park. Factor analyses revealed visits for “A place of scenic beauty”, “A place for hiking”, and “A place for the use and enjoyment by people”. Management views were to “Provide more information about plants and animals along the trails” and “Educate more about sustainability of park resources”. These results indicate a challenge to park managers to manage the park for a more deliberately improved visitor experience beyond resources protection and more toward education provided about sustainability of the resource. This can be a dilema for PNA managers because maintaining the balance between an enhanced visitor experience through additional signage can conflict with sustainability of the natural resources. This can also be a conflict because increased use can directly conflict with sustainability of the PNA (Francis, 2016; Lofthouse & Simmons, 2016). Keywords: Ecosystem Services, Protected Nature Areas, Park Management, Sustainability, Nature-based Tourism